ANALYZING THE AVIATION SECURITY KNOWLEDGE TEST ITEMS TO EVALUATE CADET PROFICIENCY ACROSS DIVERSES LEVEL OF VOCATIONAL SCHOOLS - Yune Andryani Pinem; Nikola San Fajar; Djoko Widagdo (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Assessments are vital tools in education, shaping dynamic learning experiences and contributing significantly to overall learner development. In AVSEC training, mandatory tests for license acquisition are a prerequisite for both job applicants and active duty officers contingent upon achieving satisfactory scores. Potential test takers vary in level of formal vocational education with a minimum educational requirement of a high school for job applicants. This study scrutinizes the quality of the AVSEC test, evaluating elements like difficulty index (DIF), discrimination index (DI), and distractor efficiency (DE). Serving as a comprehensive evaluative tool, it provides valuable feedback on proficiency and areas for improvement. In AVSEC item analysis, findings indicate that retaining a low category of Differential Item Functioning (DIF) may be justifiable based on item purpose. The influence of test-taker backgrounds and nuances in classical formal education is reflected in the low Discrimination Index (DI), emphasizing the need for considerations beyond intrinsic item characteristics. Challenges emerge in questions about regulations due to their overly straightforward construction, rendering the substitution of suboptimal distractors impractical. To address potential drawbacks, the training school may contemplate replacing items with similar topics, maintaining the test's purpose while enhancing item quality. This study underscores the delicate balance required in crafting effective assessments within the distinctive context of AVSEC.